How can we estimate QALYs based on PHQ-9 scores? Equipercentile linking analysis of PHQ-9 and EQ-5D. Issue 3 (2nd March 2021) - Furukawa, Toshi A; Levine, Stephen Z; Buntrock, Claudia; Ebert, David D; Gilbody, Simon; Brabyn, Sally; Kessler, David; Björkelund, Cecilia; Eriksson, Maria; Kleiboer, Annet; van Straten, Annemieke; Riper, Heleen; et al.
Abstract : Background: Quality-adjusted life years (QALYs) are widely used to measure the impact of various diseases on both the quality and quantity of life and in their economic valuations. It will be clinically important and informative if we can estimate QALYs based on measurements of depression severity. Objective: To construct a conversion table from the Patient Health Questionnaire-9 (PHQ-9), the most frequently used depression scale in recent years, to the Euro-Qol Five Dimensions Three Levels (EQ-5D-3L), one of the most commonly used instruments to assess QALYs. Methods: We obtained individual participant data of randomised controlled trials of internet cognitive-behavioural therapy which had administered depression severity scales and the EQ-5D-3L at baseline and at end of treatment. Scores from depression scales were all converted into the PHQ-9 according to the validated algorithms. We used equipercentile linking to establish correspondences between the PHQ-9 and the EQ-5D-3L. Findings: Individual-level data from five trials (total N=2457) were available. Subthreshold depression (PHQ-9 scores between 5 and 10) corresponded with EQ-5D-3L index values of 0.9–0.8, mild major depression (10–15) with 0.8–0.7, moderate depression (15–20) with 0.7–0.5 and severe depression (20 or higher) with 0.6–0.0. A five-point improvement in PHQ-9 corresponded approximately with an increase in EQ-5D-3L score by 0.03 and a ten-point improvement by approximately 0.25. Conclusions and Clinical Implications: The conversion table between the PHQ-9 and the EQ-5D-3L scores will enable fine-grained assessment of burden of depression at its various levels of severity and of impacts of its various treatments.